Six Month Abstinence Heterogeneity in the Best Quit Study. Issue 12 (22nd April 2019) - Javitz, Harold S; Bush, Terry M; Lovejoy, Jennifer C; Torres, Alula J; Wetzel, Tallie; Wassum, Ken P; Tan, Marcia M; Alshurafa, Nabil; Spring, Bonnie
Abstract : Recommendations for improving smoking cessation outcomes were made for groups of smokers with very different quitting success rates who were grouped on the basis of their individual pretreatment and treatment characteristics. Abstract: Background: Understanding the characteristics of smokers who are successful in quitting may help to increase smoking cessation rates. Purpose: To examine heterogeneity in cessation outcome at 6 months following smoking cessation behavioral counseling with or without weight management counseling. Methods: 2, 540 smokers were recruited from a large quitline provider and then randomized to receive proactive smoking cessation behavioral counseling without or with two versions of weight management counseling. A Classification and Regression Tree (CART) analysis was conducted to identify the individual pretreatment and treatment characteristics of groups of smokers with different quitting success (as measured by point prevalence of self-reported smoking of any amount at 6 months). Results: CART analysis identified 10 subgroups ranging from 25.5% to 70.2% abstinent. The splits in the CART tree involved: the total number of counseling and control calls received, whether a smoking cessation pharmacotherapy was used, and baseline measures of cigarettes per day, confidence in quitting, expectation that the study would help the participant quit smoking, the motivation to quit, exercise minutes per week, anxiety, and lack of interest or pleasure in doing things. Costs per quitter ranged from a low of US270 to a high of US630. Specific treatment recommendations are made for each group. Conclusions: These results indicate the presence of a substantial variation in abstinence following treatment, and that the total extent of contact via counseling calls of any type and baseline characteristics, rather than assigned treatment, were most important to subgroup membership and abstinence. Tailored treatments to subgroups who are at high risk for smoking following a quit attempt could increase successful smoking cessation.